Use of anticoagulants in patients with COVID-19: a living systematic review and meta-analysis - Batista, Diane R. [UNESP]; Floriano, Idevaldo; Silvinato, Antonio; Bacha, Hélio A.; Barbosa, Alexandre N. [UNESP]; Tanni, Suzana E. [UNESP]; Bernardo, Wanderley M. (Sociedade Brasileira de Pneumologia e Tisiologia, 2022)
Objective: To answer questions related to the use of anticoagulants in the treatment of COVID-19 patients. Methods: This was a systematic review and meta-analysis of phase 3 randomized controlled trials comparing the use of anticoagulants in non-hospitalized and hospitalized COVID-19 patients. We searched the following databases: MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov from their inception to January 22, 2022. The risk of bias was assessed by the Cochrane risk-of-bias tool, and the quality of evidence was assessed by the Grading of Recommendations Assessment, Development and Evaluation system. Results: A total of 401 studies were initially selected. Of those, 9 met the inclusion criteria and were therefore analyzed (a total of 6,004 patients being analyzed). In non-hospitalized COVID-19 patients, no significant difference was found between post-discharge prophylactic anticoagulation and no intervention regarding venous thromboembolism or bleeding at 30 days. In hospitalized COVID-19 patients, full anticoagulation resulted in a slight reduction in thrombotic events at 30 days (risk difference, −0.03; 95% CI, −0.06 to −0.00; p = 0.04; I2 = 78%), the quality of evidence being moderate. However, no significant difference was found between full anticoagulation and no intervention regarding the risk of major bleeding, the quality of evidence being very low. No significant difference was found between intermediate-and standard-dose prophylactic anticoagulation (risk difference, −0.01; 95% CI, −0.07 to 0.06; p = 0.81; I2 = 0%), the quality of evidence being very low. Conclusions: Therapeutic anticoagulation appears to have no effect on mortality in COVID-19 patients, resulting in a slight reduction in venous thromboembolism in hospitalized patients.
Keywords: Anticoagulants; COVID-19; SARS-CoV-2